A Digital World: Role of Electronic Invoice for Personal Taxpayer Compliance - Meilinda Stefani Harefa; Amran Manurung; Eldaa Yuannda Harefa (Postgraduate, University of Mataram, 2023)
The digital world has inevitably entered various fields of human life in carrying out their duties as world leaders. Technology is an important tool to ease the human workload, including in this discourse is human resource management. This study aims to reveal the perceptions of Taxable Entrepreneurs (PKP) and the Tax Service Office (KPP) on the implementation of e-invoicing and the impact of e-invoicing on taxpayer compliance. The focus of this research is to reveal PKP's perception of the implementation of e-invoicing from the aspects of inputting, data processing, and output. KPP perceptions from the aspects of tax administration and tax evidence, and taxpayer compliance assessed from the aspects of calculation, deposit and reporting. This research is qualitative research with a case study approach. Data analysis is carried out interactively starting from data collection, data reduction, data presentation, and conclusion drawing. According to PKP, the advantages of e-invoicing are more efficient processing time, more accurate tax calculation results, easier and safer storage because it has a QR code, but the weaknesses of e-invoicing are repetitive work in inputting input tax values, the system is not yet able to read invoice codes and the application is vulnerable to viruses. According to KPP, the application of e-invoicing is very helpful for the tax office in fully controlling in real time all tax invoices uploaded and reported by PKP. From the research results, there is not enough evidence that e-invoicing has an impact on improving taxpayer compliance, especially in tax calculations. According to the Tax Office, the application of e-invoicing can improve taxpayer administrative compliance in terms of calculating, depositing and reporting so that tax revenue will be increased.